Central nervous system involvement in children and adolescents with rhabdomyosarcoma. A report from the AIEOP Soft Tissue Sarcoma Committee. Issue 4 (27th March 2018) - Pierobon, Marta; Ferrari, Andrea; Scarzello, Giovanni; Tamburini, Angela; Quaglietta, Lucia; Ruggiero, Antonio; Milano, Giuseppe Maria; Zin, Angelica; Bisogno, Gianni
Abstract: Background: Rhabdomyosarcoma (RMS) is a highly malignant tumor typically affecting children and adolescents. Central nervous system (CNS) dissemination is rare in RMS patients, but seems to have a particularly negative impact. The aim of this study was to analyze treatment and outcome of patients with RMS and evidence of CNS disease who were registered in the protocols coordinated by the Italian Soft Tissue Sarcoma Committee from March 1979 to December 2016. Methods: We analyzed 39 patients with CNS disease. Depending on when their CNS disease was identified, we grouped patients as: Group A, at diagnosis; Group B, progression during treatment; Group C, at first relapse. Results: Six patients were in Group A (2.7% of metastatic RMS patients at diagnosis); 24 were in Group B and 9 in Group C (6.5% of patients with tumor progression/relapse included in the protocols). Only 5 patients (4 in Group A, 1 in Group B) survived the event and are alive in complete remission with a median follow-up of 17.5 years. These 5 patients received systemic chemotherapy and craniospinal radiotherapy, and 2 of them also received intrathecal therapy with topotecan. Conclusions: CNS involvement at diagnosis is a rare and prognostically negative event in RMS patients, but not always fatal when it is found at diagnosis. It is more frequent during or shortly after treatment, and the more dismal prognosis in these cases underscores the need to improve our ability to identify patients at risk of CNS dissemination in order to attempt more effective treatments that can sterilize the meninges.